Evolution of mate choice and the so‐called magic traits in ecological speciation. (19th June 2013) - Thibert‐Plante, Xavier; Gavrilets, Sergey
Abstract: Non‐random mating provides multiple evolutionary benefits and can result in speciation. Biological organisms are characterised by a myriad of different traits, many of which can serve as mating cues. We consider multiple mechanisms of non‐random mating simultaneously within a unified modelling framework in an attempt to understand better which are more likely to evolve in natural populations going through the process of local adaptation and ecological speciation. We show that certain traits that are under direct natural selection are more likely to be co‐opted as mating cues, leading to the appearance of magic traits (i.e. phenotypic traits involved in both local adaptation and mating decisions). Multiple mechanisms of non‐random mating can interact so that trait co‐evolution enables the evolution of non‐random mating mechanisms that would not evolve alone. The presence of magic traits may suggest that ecological selection was acting during the origin of new species.